Owls in our yard! : the story of Alfie - Safina, Carl, 1955- (Norton Young Readers, an imprint of W. W. Norton & Company, 2024)
"A baby owl is rescued and rehabilitated, and builds her own family, in this tender and wise picture book. In the spring of 2019, ecologist Carl Safina and his wife, Patricia, took in little Alfie, a bedraggled Eastern Screech Owl chick who quickly became part of their family. With the Safinas' care and expertise, the little owl grew, learned to hunt on her own, and eventually found her own family in a mate and chicks. As time passed, Carl realized that his bond with Alfie was greater than just saving her life--it offered wisdom, joy, and magic to him in return. Carl Safina lends an insightful and expert voice to Alfie's tale, providing readers with a perspective that is simultaneously informative and deeply personal. With eye-catching, intimate photographs chronicling Alfie's healing and growth, Owls in Our Yard is the heartfelt story of an animal/human friendship rooted in trust, care, and respect for the natural world."--Amazon.